A dual approach for modelling and optimisation of industrial urea reactor: Smart technique and grey box model. (26th April 2013) - Zendehboudi, Sohrab; Zahedi, Gholamreza; Bahadori, Alireza; Lohi, Ali; Elkamel, Ali; Chatzis, Ioannis
Abstract Urea has the highest demand among all solid nitrogenous fertilisers within the agriculture industry. In this paper, a mathematical model and an Artificial Neural Network (ANN) technique are proposed for the simulation and optimisation of the urea plant in an industrial petrochemical company. The developed mathematical model consists of complex vapour–liquid equilibria for the NH3–CO2–H2O–(NH2)2CO system in thermodynamic and reaction frameworks. The smart technique (e.g. ANN) considers the CO2 conversion in terms of temperature and the molar ratios of NH3/CO2 and H2O/CO2 in the liquid phase. The ANN predictions were compared with the real data and results obtained from the mathematical model. An acceptable agreement was attained between deterministic methods. Through implementation of a systematic sensitivity analysis, it was found that a temperature of 191°C, a pressure of 132 atm and a NH3/CO2 ratio of 2.7 are the optimum process conditions for the urea production. It is concluded that the developed ANN (or connectionist) technique is an efficient tool for modelling complex phase equilibria with reaction in the industrial urea plant.